High-Harmonic Generation in an Optical Fiber Functionalized with Zinc Oxide Thin Films - Idris Tiliouine; Yann Leventoux; Jean-Christophe Orlianges; Aurelian Crunteanu; Marie Froidevaux; Hamed Merdji; Sébastien Février (Photonics)
High-order harmonic generation (HHG) in semiconductor thin films from ultrashort mid-infrared laser drivers holds the potential for the realization of integrated sources of extreme ultraviolet light. Here, we demonstrate solid-state HHG in zinc oxide thin films synthesized by the radiofrequency reactive magnetron sputtering process directly on the cleaved facets of optical fibers. Harmonics 3 to 13 of the radiation from a fiber-based laser system delivering 500 kW, 96 fs pulses at 3130 nm are produced in the thin film and guided along the fiber. A proper choice of the laser wavelength and fiber material allows for filtering out the mid-IR pump laser and achieving the HHG mode selection. The possibility to nanostructure the fiber exit by, e.g., focused ion beam milling paves the way to an increased control over the HHG spatial mode.